EVALUATION OF BIOCHEMICAL PROFILE OF CHRYSIN IN STREPTOZOTOCIN –NICTONIMAIDE INDUCED DIABETIC RATS - ANITHA.T.A; RAJADURAI. M (International Journal of Pharma and Bio Sciences, 2015)
To evaluate the effect of Chrysin, a flavone, biologically active compound extracted from many plants, honey and propolis on Streptozotocin(STZ) – nicotinamide induced diabetic rat models. On administration of graded doses of Chrysin (25, 50 &100 mg/Kg body wt.) to normal and diabetic rats for 45 days, a significant (p<0.05) reduction in the levels of blood glucose, urea, uric acid and creatinine. The treatment with Chrysin significantly increased the level of total protein, albumin and bilirubin. Significant changes were also observed in plasma lipid profile in Chrysin treated diabetic control and normal animals. This present investigation suggests that for all the above biochemical studies performed, Chrysin treated rats showed more hypoglycemic activity.